EVALUATION OFFIVER PERFORMANCE OF NAVIGATION AID FACILIES (NAF) BEACON LIGHT IN THE RIAU STRAIT AREA - Priyono, Broto; Lopulalan, Pierre Marcello; Sidartha, Driakoro Budi; Agustini, Elfita; Syahputri, Cindy Maretha Indah; Apriani, Dahlia Dewi (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
The Beacon Light in the work area of the Tanjungpinang Type A Class I Navigation District is in the Riau Strait Region Beacon Light. Based on the results of the analysis, it is known that there are still many discrepancies in the Auxiliary Means of Navigation at the Riau Strait Regional Beacon Light with the regulation of the Minister of Transportation Number PM 25 of 2011 concerning Auxiliary Means of Navigation. This research aims to determine the suitability of the Auxiliary Navigation Officer and Fulfillment of the Needs of the Auxiliary Navigation Officer to improve the Competence of the Auxiliary Navigation Officer so that the Performance of the Beacon Light in the Riau Strait Region runs smoothly. The data analysis used is qualitative on primary data through documentation and interviews and secondary data in the study of legislation and books related to this research. Evaluation of Aids to Navigation in the Riau Strait Region is an important first step to create a qualified Aids to Navigation in accordance with the Minister of Transportation Regulation No. 25 of 2011. The results of this study can provide information about the suitability of Competence and the Number and fulfillment of the needs of Auxiliary Navigation Officers. The addition of personnel, training and education as well as the needs for Auxiliary Navigation Officers also need to be considered in order to create Auxiliary Navigation Officers in accordance with the Minister of Transportation Regulation No. 25 of 2011 concerning Auxiliary Navigation and create a smooth performance of the Riau Strait Region Beacon Light.